Dual‐polarized frequency selective rasorber with broadband absorption and transmission. Issue 2 (4th November 2021) - Li, Yufan; Kou, Na; Yu, Shixing; Ding, Zhao; Zhang, Zhengping
Abstract: In this letter, a polarization‐insensitive frequency selective rasorber (FSR) is proposed, which can achieve wide absorption band and wide transmission band at low frequency and high frequency, respectively. It consists of two layers and an air spacer in the middle. The top layer is a resistive sheet, which is realized by an improved Jerusalem metal strip loaded with lumped resistors, while a square ring slot‐type bandpass FSS on the bottom is designed to match the passband of the resistive sheet. The working principle of the FSR is analyzed by the method of equivalent circuit. In order to verify our design, a sample prototype has been fabricated and measured, it can be seen from the measurement results that an insertion loss of about 0.12 dB is obtained at 21.6 GHz under normal incidence, the 1 dB transmission relative bandwidth and the relative bandwidth for 10 dB absorption reaches more than 80% and 24%, respectively. The FSR exhibits the characteristics of insensitivity to polarization with excellent angle stability. The simulation results and the measured results are relatively consistent, whether it is normal incidence or oblique incidence. The proposed FSR has the potential to be used in the applications of stealth performances improved of low‐observable platforms in the future.